Roles and contributions of community seed banks in climate adaptation in Nepal. Issue 2 (17th February 2018) - Maharjan, Shree; Maharjan, Keshav
ABSTRACT: Community seed banks are an effective local institution to conserve quality seeds, to strengthen farmers' accessibility to social seed networks, and improve agrobiodiversity and food security. This article analyses the prospects and challenges of community seed banks in climate change contexts. It finds that community seed banks serve as sources of climate-resilient seeds to withstand in local climates and improve community resilience. Community seed banks provide landraces for participatory crop improvement to develop resistant varieties to improve quality and productivity. They also strengthen participatory seed exchange to cope with climate adversity. However, there are challenges with defining specific and common goals, functions, approaches, and governance.